Enhancing Collaboration Skills Through STEM-Based e-LKPD: Integrating Palembang's Local Wisdom into Learning - Khotimah, Masayu Husnul; Wiyono*, Ketang; Sriyanti, Ida; Rahman, Nor Farawahidah Abdul (Universitas Syiah Kuala, 2025)
Collaboration skills are an important aspect in equipping students to face the challenges of the 21st century. This ability supports the creation of active and effective learning, while fostering an attitude of cooperation, responsibility, and a deeper understanding of the subject matter, therefore the purpose of this study was conducted to analyze the effectiveness of science, technology, engineering, and mathematics, based students worksheet (LKPD) integrated with Palembang local wisdom in improving the collaboration of high school students. This study at SMA Negeri 2 Palembang involved 48 students with a one-group pretest-posttest design. The results showed a significant increase in collaboration skills, with an average pretest score of 52.5 increasing to 86.35 in the posttest and N-gain of 0.71 (high category). Indicators of responsibility, flexibility, and mutual respect also increased. Effect size analysis showed a large impact on physics learning, especially on the aspect of mutual respect. This finding confirms that the developed LKPD is effective in improving students' collaboration skills.